The Effect of Spirituality Methods on Resilience in Drug Users in Ar-Rahman Palembang - Awang Kurniawan; Dwi Hurriyati (Budapest International Research and Critics University, 2022)
Increased drug use information from the National Narcotics Agency (BNN) in 2017 experienced an increase in drug use, in 2019 Ar-Rahman's drug use was 34.02% in 2020 by 24.74% until 2021 there was an increase in drug abuse carrying out rehabilitation in Ar -Rahman. Ar Rahman Palembang. In 2021 there will be a significant increase to 41.24% because during this pandemic many people have difficulty in carrying out their activities and many experience layoffs (PHK) so that many people use drugs as an alternative to calm themselves from adversity. This is due to the limited direction. and can't do anything. So for this situation one needs the ability to make and adapt to difficult circumstances and fulfill different demands throughout daily life. This capacity in psychology is known as resilience. Rehabilitation performs various ways to awaken users from drug use, one of which is by providing spirituality. It is not only mental issues that must be considered but also otherworldly abilities to take on an important role. Without spirituality in humans, their lives would feel endlessly empty, they would face adversity while dealing with issues that hindered their psychological research, and more lethally, people would lose the significance of life.